Ideal Kingship in Ugarit and Israel / dmṿt hmlṿkhh vʾṿgryt vhshṿʾh ldmṿt hmlṿkhh vyshrʾl - Safran, Jonathan D. (Bet miḳra, 1975)
The kingdom which existed in Ugarit in the Late Bronze Age has considerable importance for Ancient Israel, for, when the Israelites chose to institute a monarchy, they did not independently create all the patterns of royal rule. As we learn from I Samuel 8 : 5, where the people demand of Samuel : "Now appoint us a king to judge us like all the nations", Israel borrowed such patterns from her neighbors in Syro-Palestine, adapting them to her own character, culture, and experience. Though Ugarit no longer existed at that time, it certainly represented part of the same cultural milieu. The purpose of this paper being to compare Ugaritic and Israelite concepts of ideal kingship, I have chosen the literary-epic texts of Ugarit and the royal and enthronement psalms of the Bible as a basis for comparison. The Ugaritic literary texts, which include legends, myths, and ritual texts, are the result of a lengthy process of literary development. They represent a tendential selection of characteristics which, to the writers of the texts, characterized what was important in kingship. We can thus speak of ideal kingship, or the image of kingship, in the literary-epic texts. A parallel picture of Israelite kingship is presented in the royal and enthronement psalms, which, like the Ugaritic literary-epic sources, were of cultic-official character (not so the historiographic and prophetic materials which deal with kingship). The aspects of kingship compared here are : the source of royal authority and its transfer; the special relationship between god and king; the non-cultic duties of the king as judge, administrator, and military commander; the cultic functions of priest, oracle, and bestower of fertility. The possibility of royal participation in cultic drama is discussed in Chapter 7. Chapter 8 lists and compares words, terms, titles, and symbols of kingship in Ugarit and Israel. A discussion of the similarities and differences between Ugaritic and Israelite kingship concludes the article.